2007
DOI: 10.1590/s1516-35982007000500018
|View full text |Cite
|
Sign up to set email alerts
|

Composto exaurido do cogumelo Agaricus blazei na dieta de frangos de corte

Abstract: RESUMO -Avaliou-se o efeito da substituição de um antibiótico por diferentes níveis do composto exaurido do cogumelo (CEC) Agaricus blazei sobre o desempenho de frangos de corte de 1 a 42 dias de idade. Foram avaliadas sete dietas, seis com adição de CEC (0,0; 0,2; 0,4; 0,6; 0,8 e 1,0%) e uma com antibiótico (avilamicina 10 ppm). Foram utilizados 588 pintos de 1 dia de idade, distribuídos em um delineamento inteiramente casualizado, com seis repetições por dieta (três por sexo) e 14 aves por unidade experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…Garlic has antioxidant, antimicrobial and antiviral properties (Corzo-Martinez et al 2007). Oyester mushroom (Pleurotus ostreatus) are known to have antioxidant and immunomodulatory effects (Shamtsyan et al 2007 andElmastas et al 2007) and has been shown to improve growth, immunity and intestinal health (Guo et al 2003;Machado et al 2007 andGiannenas et al 2010). Propolis is a resinous substance which worker bees collect from various sources to seal hive grooves and mummify dead invaders (Burdock, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Garlic has antioxidant, antimicrobial and antiviral properties (Corzo-Martinez et al 2007). Oyester mushroom (Pleurotus ostreatus) are known to have antioxidant and immunomodulatory effects (Shamtsyan et al 2007 andElmastas et al 2007) and has been shown to improve growth, immunity and intestinal health (Guo et al 2003;Machado et al 2007 andGiannenas et al 2010). Propolis is a resinous substance which worker bees collect from various sources to seal hive grooves and mummify dead invaders (Burdock, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados utilizando polissacarídeos, purificados ou não, na tentativa de substituir os antibióticos na avicultura, e os resultados observados são promissores (FUINI, 2001;GUO;ALI, QURESHI, 2003;MACHADO et al, 2007). Entre os aditivos estudados, a Carboximetilglucana (CMG) pode ser uma importante alternativa devido a sua capacidade de ativar de forma não específica os componentes humoral e celular do sistema imune do hospedeiro (TZIANABOS, 2000).…”
Section: Introductionunclassified
“…Most commonly, the research on SMS has focused on the enzymatic activity of the residual mycelium and its ability to produce lignocellulosic enzymes such a laccase, xylanase, lignin peroxidase, cellulose and hemicellulose as a cheap source of bioremediation, animal feed and energy feedstock [12,13]. The advantages of using SMS as a soil fertilizer over chemical fertilizer include the fact that it delivers a slow-release of nutrients that will not burn crops upon application.…”
Section: Introductionmentioning
confidence: 99%